Adsorption Characteristics of Dietary Fibres from Sea Buckthorn Pomace on Acrylamide - Weiran CUI; Mengling LÜ; Hongyu BAI; Yue SUN; Hui WANG; Meili SHAO (Shipin gongye ke-ji)
To explore the influencing factors and adsorption stability of seabuckthorn pomace dietary fiber in adsorbing acrylamide (AA), as well as to fit the adsorption process using isothermal adsorption model and kinetic model. Results indicated that the adsorption rate increased with the addition of seabuckthorn pomace dietary fiber and the extension of adsorption time. However, as the concentration of AA, system temperature, and system pH increased, the adsorption rate initially increased and then decreased. When the seabuckthorn pomace dietary fiber addition was 8 mg/mL, AA concentration was 4 µg/mL, pH was 5, temperature was 35 ℃, and adsorption time was 8 h, the adsorption rate was at its maximum, the adsorbed amount was 44.8 µg/g. Moreover, the seabuckthorn pomace dietary fiber-AA complex exhibited good stability both in vitro and in vivo. In the gastric environment, with a pH of 1.5~2.5 and a digestion time of 1~2 h, the seabuckthorn pomace dietary fiber-AA complex remained relatively stable, shen mewith an AA release rate of 0~12.28%. In the intestinal environment, with a bile salt concentration of 0.1% and a digestion time of 3 h, the seabuckthorn pomace dietary fiber-AA complex showed the best stability, with an AA release rate of 14.75%. Additionally, both the Langmuir (R2=0.93) and Freundlich (R2=0.90) isothermal adsorption models, as well as the pseudo-second-order kinetic model (R2=0.94), fitted the adsorption process of AA by seabuckthorn pomace dietary fiber well, indicating the presence of both physical and chemical adsorption. This study lays the foundation for the application of seabuckthorn pomace dietary fiber in AA adsorption detoxification.